The Linguistic Risk-Taking Initiative for Academic Short-Term Study Abroad (k:ON - Kölner Online Journal für Lehrer*innenbildung, 2026)
This article outlines the implementation and evaluation of the Linguistic Risk-Taking (LRT) Initiative (Slavkov & Séror, 2019) for German learners on short-term academic excursions. The initiative encourages students to step outside their linguistic comfort zones by engaging in small, authentic linguistic risks, referred to here as 'challenges'. These challenges are documented in an adapted version of the LRT passport, the Studienreisepass (STRP), which was piloted with A2-level learners from France, Spain, Portugal, and Italy, and refined through an action research cycle. A mixed-methods research design combining questionnaires, STRP records, observations, and interviews was used to examine the influence of the STRP on learners' perceived language proficiency and Willingness to Communicate (WTC). The findings suggest that the STRP may foster both, particularly when embedded in a structured pedagogical framework, and that it is especially effective for learners with higher levels of autonomy and self-regulation.
Keywords: Linguistic Risk-Taking (LRT); German as a Second/Additional Language (Deutsch als Fremdsprache (DaF); Short-Term Study Abroad; Willingness to Communicate (WTC); Gamification